A shRNA Functional Screen Reveals Nme6 and Nme7 Are Crucial for Embryonic Stem Cell Renewal123. (20th September 2012) - Wang, Chia‐Hui; Ma, Nianhan; Lin, Yu‐Tsen; Wu, Cheng‐Chung; Hsiao, Michael; Lu, Frank Leigh; Yu, Ching‐Chia; Chen, Shao‐Yin; Lu, Jean
Abstract: In contrast to the somatic cells, embryonic stem cells (ESCs) are characterized by its immortalization ability, pluripotency, and oncogenicity. Revealing the underlying mechanism of ESC characteristics is important for the application of ESCs in clinical medicine. We performed systematic functional screen in mouse ESCs with 4, 801 shRNAs that target 929 kinases and phosphatases. One hundred and thirty‐two candidate genes that regulate both ESC expansion and stem cell marker expression were identified. Twenty‐seven out of the 132 genes were regarded as most important since knockdown of each gene induces morphological changes from undifferentiated to differentiated state. Among the 27 genes, we chose nonmetastatic cell 6 (Nme6, also named as Nm23‐H6) and nonmetastatic cell 7 (Nme7, also designated as Nm23‐H7) to study first. Nme6 and Nme7 both belong to the members of nucleoside diphosphate kinase family. We demonstrate that Nme6 and Nme7 are important for the regulation of Oct4, Nanog, Klf4, c‐Myc, telomerase, Dnmt3B, Sox2, and ERas expression. Either knockdown of Nme6 or Nme7 reduces the formation of embryoid body (EB) and teratoma. The overexpression of either Nme6 or Nme7 can rescue the stem cell marker expression and the EB formation in the absence of leukemia inhibiting factor. This implies the importance of Nme6 and Nme7 in ESC renewal. This finding not only pinpoints Nme6 or Nme7 can regulate several critical regulators in ESC renewal but also increases our understanding of the ESC renewal and oncogenesis. STEM Cells 2012;30:2199–2211